Structural and functional characterization of the dry forest in central Argentine Chaco - Benedictto, Mariana N.; Gómez-Valencia, Bibiana; Torrella, Sebastián A. (Instituto de Ecología, A.C., 2019)
Here, we studied the composition, structure and functioning of the woody vegetation of a 1000-ha area of the Central Argentine Chaco. First, we identified, through Landsat satellite image processing, three different vegetation classes: two forest types and a savanna. Each class was field surveyed to analyze the composition and structure of the woody plant community. Functioning was assessed through the enhanced vegetation index – a proxy of productivity – obtained from the MODIS sensor. The forest classes showed no differences in composition but some differences in structural attributes, particularly in the density of the dominant tree species in the area, Aspidosperma quebracho-blanco. As expected, the savanna showed less density and basal area of woody plants, with a relative high proportion of tree species seedlings and heliophilous shrubs. The forest class with less density of A. quebracho-blanco presented higher productivity. This could be related to a higher ability of the shrub layer to intercept radiation because shrubs are under an open canopy, as has been noted for early successional stages. Additionally, we found that annual mean productivity for the three classes showed a negative trend in the period 2000-2014. Our results provide valuable information since there are no studies addressing relationships between structural and functional attributes at local level in the Chaco Region.